An analysis of household waste generation in the Fomento 2 Public Housing Complex, Comoro Village, Dili, Timor Leste - Silva Augusto Almeida da; Maryono Maryono; Hermawan Ferry (E3S Web of Conferences)
Garbage can be defined as the residual material by humans in their daily activities. It is inevitable that the generation of waste will continue to increase in line with the continued interaction of humans in the real world. The purpose of this study is to analyze the generation of waste in the Fomento 2 housing complex and to identify the factors that influence it. The method applied in this scientific analysis is descriptive quantitative. There are several scientific articles that are used as reading material to support the study and strengthen data analyzes. The result of this study demonstrated that the quantity of waste generated was 177.1 kg, then sorted according to type, and found a totalreduction of 93.2 kg, with an average reduction of up to 53.09%. The data demonstrate that the generation of waste in the Fomento 2 housing complex is a significant concern. The lack of access to waste sorting containers and the lack of community skills in processing waste properly and correctly. And it’s require urgent attention to ensure the maintenance of a healthy life and a good environmental quality.